Effects of red clover isoflavones on tall fescue seed fermentation and microbial populations in vitro - Melchior, Emily A.; Smith, Jason K.; Schneider, Liesel G.; Mulliniks, J. Travis; Bates, Gary E.; McFarlane, Zachary D.; Flythe, Michael D.; Klotz, James L.; Goodman, Jack P.; Ji, Huihua; Myer, Phillip R. (PloS one, 2018)
Negative impacts of endophyte-infected Lolium arundinaceum (Darbyshire) (tall fescue) are responsible for over $2 billion in losses to livestock producers annually. While the influence of endophyte-infected tall fescue has been studied for decades, mitigation methods have not been clearly elucidated. Isoflavones found in Trifolium pratense (red clover) have been the subject of recent research regarding tall fescue toxicosis mitigation. Therefore, the aim of this study was to determine the effect of ergovaline and red clover isoflavones on rumen microbial populations, fiber degradation, and volatile fatty acids (VFA) in an in vitro system. Using a dose of 1.10 mg × L-1, endophyte-infected or endophyte-free tall fescue seed was added to ANKOM fiber bags with or without 2.19 mg of isoflavones in the form of a control, powder, or pulverized tablet, resulting in a 2 × 3 factorial arrangements of treatments. Measurements of pH, VFA, bacterial taxa, as well as the disappearance of neutral detergent fiber (aNDF), acid detergent fiber (ADF), and crude protein (CP) were taken after 48 h of incubation. aNDF disappearance values were significantly altered by seed type (P = 0.003) and isoflavone treatment (P = 0.005), and ADF disappearance values were significantly different in a seed × isoflavone treatment interaction (P ≤ 0.05). A seed × isoflavone treatment interaction was also observed with respect to CP disappearance (P ≤ 0.05). Eighteen bacterial taxa were significantly altered by seed × isoflavone treatment interaction groups (P ≤ 0.05), eight bacterial taxa were increased by isoflavones (P ≤ 0.05), and ten bacterial taxa were altered by seed type (P ≤ 0.05). Due to the beneficial effect of isoflavones on tall fescue seed fiber degradation, these compounds may be viable options for mitigating fescue toxicosis. Further research should be conducted to determine physiological implications as well as microbiological changes in vivo.